Geographic and socioeconomic variation of sodium and potassium intake in Italy: results from the MINISAL-GIRCSI programme - Simona Giampaoli; Francesco P Cappuccio; Chen Ji; Luigi Palmieri; Diego Vanuzzo; Chiara Donfrancesco; Renato Ippolito; Pasquale Strazzullo (BMJ Open)
Objectives To assess geographic and socioeconomic gradients in sodium and potassium intake in Italy.Setting Cross-sectional survey in Italy.Participants 3857 men and women, aged 39–79 years, randomly sampled in 20 regions (as part of a National cardiovascular survey of 8714 men and women).Primary outcome measures Participants’ dietary sodium and potassium intakes were measured by 24 h urinary sodium and potassium excretions. 2 indicators measured socioeconomic status: education and occupation. Bayesian geoadditive models were used to assess spatial and socioeconomic patterns of sodium and potassium intakes accounting for sociodemographic, anthropometric and behavioural confounders.Results There was a significant north-south pattern of sodium excretion in Italy. Participants living in southern Italy (eg, Calabria, Basilicata and Puglia >180 mmol/24 h) had a significantly higher sodium excretion than elsewhere (eg, Val d'Aosta and Trentino-Alto Adige <140 mmol/24 h; p<0.001). There was a linear association between occupation and sodium excretion (p<0.001). When compared with occupation I (top managerial), occupations III and IV had a 6.5% higher sodium excretion (coefficients: 0.054 (90% credible levels 0.014, 0.093) and 0.064 (0.024, 0.104), respectively). A similar relationship was found between educational attainment and sodium excretion (p<0.0001). When compared with those with a university degree, participants with primary and junior school education had a 5.9% higher urinary sodium (coefficients: 0.074 (0.031, 0.116) and 0.038 (0.001, 0.075), respectively). The socioeconomic gradient explained the spatial variation. Potassium excretion was higher in central regions and in some southern regions. Those in occupation V (low-skill workers) showed a 3% lower potassium excretion compared with those in occupation I. However, the socioeconomic gradient only partially explained the spatial variation.Conclusions Salt intake in Italy is significantly higher in less advantaged social groups. This gradient is independent of confounders and explains the geographical variation.